Evaluation of the alternating magnetic field (AMF) influence in catalytic activities of enzymes immobilized into magnetic graphene oxide: A new approach - Cardoso Pinto, Gabriel [UNESP]; Lucena, Guilherme Nunes [UNESP]; Debone Piazza, Rodolfo [UNESP]; Lopes Costa, João Miguel; Coimbra e Silva, Eduardo Torres Couto; Gu, Yuanyu; de Paula, Ariela Veloso [UNESP]; Silva, Nuno João Oliveira; Costa Marques, Rodrigo Fernando [UNESP] (Elsevier, 2023)
The conventional methods of production of biofuels generate hazardous by-products, one way to reduce them, by using reusable enzymatic process that requires insoluble enzyme carriers. This investigation allowed the obtention of magnetic graphene oxide (MGO) carrier containing aminosilane functional groups with and without the crosslinker glutaraldehyde. Thus, it was possible to immobilize cellulases and lipases enzymes and evaluate its enzymatic activity in normal conditions, as well as the novelty that was under alternating magnetic field (AMF) conditions. Through enzymatic essays it was determined the optimal working activities for both enzymes using these two magnetic carriers, being pH 4 and 60ºC for cellulases and pH 5 and 50ºC for lipase. Different frequencies were used during AMF test (20, 30, 50 and 70 kHz) and it was confirmed for both groups that with the increase in frequency during the reaction, the less pronounced will be the activity decrease at pH values different from the optimal condition. Due to magnetic properties from the carrier and the medium reaction used the recycle test was satisfactory for the two immobilized groups of the cellulase enzyme, being recycled 9 times without losses greater than 50 % of relative activity. As for the two groups of immobilized lipases, drastic decreases in activity were observed, possibly caused by the strong enzyme/substrate interaction. For both groups of immobilized enzymes, an inhibitory behavior of the glutaraldehyde reagent, widely used as an enzyme/carrier cross-linker, was also observed. Nevertheless, the immobilization of cellulase and lipases enzymes into MGO derivates shows a promising and suitable strategy for the conversion of cellulose and long-chain acyl esters into value-added inputs.
Keywords: Alternating magnetic field; Enzyme immobilization; Magnetic graphene oxide